The Five-Year-Old is Fabulous! - Heidi Liss Radunovich (EDIS)
FCS-2274, a 5-page fact sheet by Heidi Liss Radunovich, reviews typical physical, social, emotional, and intellectual development for 5-year-old children, and gives tips on understanding and disciplining children in this age group. Published by the UF Department of Family, Youth and Community Sciences, July 2007.